Time-dependent analysis of simply supported and continuous unbonded prestressed concrete beams. (1st August 2021) - Páez, Pablo M.; Sensale-Cozzano, Beradi
Highlights: Prestress loss in continuous unbonded prestressed concrete beams is analyzed. An equation to estimate the prestress loss is proposed. A numerical model based on the finite element method is developed. The approach is used for the time-dependent analysis of unbonded prestressed concrete beams. Numerical and experimental results are compared. The proposed equation successfully predict the prestress loss. The approach is capable of replicating the behavior over time of unbonded prestressed concrete beams. Abstract: An equation to estimate the prestress loss in continuous unbonded prestressed concrete beams is proposed in this paper. The equation accounts for the creep and shrinkage of the concrete and the relaxation of the prestressing steel. In addition, a numerical model is developed based on the finite element method for the time-dependent analysis of these types of concrete beams. The approach also accounts for the presence of non-prestressed steel reinforcement and the friction between the tendons and their ducts. Furthermore, a well-justified integral-form equation is proposed to compute the strain at each section of the unbonded prestressing steel accounting for the friction between the tendons and their ducts. This equation is based on the equation for frictional loss accepted by different standards. The strain at each section of the unbonded prestressing is calculated from the strain in the concrete at the level of the prestressed tendon along the whole beam. Numerical and experimental results are compared to validate the proposed equation and the finite element approach and the good performance of both in modelling the behaviour of this type of prestressed concrete member over time is shown.